An Exploratory Study: The Impact of Terrorism on Risk Perceptions. An Analysis of the German Market Behaviours and Attitudes Towards Egypt. Issue 1 (2nd January 2021) - Isaac, Rami K.
ABSTRACT: The aim of this research is to get a better understanding of the influence of terrorism on risk perceptions and attitudes of the German travel behaviour towards Egypt. The research process involved an online self-administered method created with one of the leading research and web based survey tools called Qualtrics. The questionnaire filled in by 171 respondents. Findings indicate that Egypt is generally perceived as an unsafe destination to travel to, however, those respondents with Past Travel Experience (PTE) rate the country's attractiveness higher and are therefore, more likely to revisit as well. Spillover effect was found to be significant, as well as the influence of several socio- demographic factors. Risk reduction strategies were generally rated to be effective and could therefore have implications for Destination Management Organisations (DMOs) to create a more appealing image for Egypt as a holiday destination.